2009
DOI: 10.1007/s11065-008-9080-z
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of Alcohol Dependence. From Jellinek to Genetics and Beyond

Abstract: The goal of typology research is to identify subtypes of alcohol dependent (AD) patients sharing fundamental characteristics and try to match each subtype, with the most precise treatment strategy. This review provides a comprehensive history of the literature on alcohol dependent subtypes starting from the earliest attempt made by Jellinek. The binary models identified most closely with Cloninger and Babor as well as the successively more complex classifications are discussed. Typology classification potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
133
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(143 citation statements)
references
References 81 publications
5
133
0
5
Order By: Relevance
“…Environmental and genetic features contribute both to the pattern of alcohol consumption and to the risk of ADS 1 . Patients with alcohol related disorders (ARD) differ in many traits, such as age of onset of heavy drinking (early or late), patterns of drinking (continuous or binge), rate of alcohol metabolism, susceptibility to intoxication, presence or absence of comorbid psychiatric illness and rapidity of progression to medical problems 2 . The heterogeneity of clinical presentation of ARD -which include relevant differences according to their gender 3 -has justified efforts to classify them into subtypes that refine diagnosis and may give support to tailored treatment designs and better established prognosis [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental and genetic features contribute both to the pattern of alcohol consumption and to the risk of ADS 1 . Patients with alcohol related disorders (ARD) differ in many traits, such as age of onset of heavy drinking (early or late), patterns of drinking (continuous or binge), rate of alcohol metabolism, susceptibility to intoxication, presence or absence of comorbid psychiatric illness and rapidity of progression to medical problems 2 . The heterogeneity of clinical presentation of ARD -which include relevant differences according to their gender 3 -has justified efforts to classify them into subtypes that refine diagnosis and may give support to tailored treatment designs and better established prognosis [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Even though Babor's binary typology of alcoholism has been repeatedly used in researches in this field, it has not yielded consistent results as far as its clinical and epidemiological usefulness, as expected of medical typologies 4,[15][16][17][18][19] . It has been suggested that future typological research should strive to identify the limitations of actual classifications, highlight their differences and explore the consistencies they might share, to move towards a more effective routine clinical use 2,20 . The objective of this study was to replicate Babor's Typology and to explore clinical features related to personality traits that may underlie this classification of ADS patients, in order to improve its therapeutic possibilities.…”
mentioning
confidence: 99%
“…Substance abuse typologies are used to diagnose addiction disorders, provide information regarding psychological and neurobiological mechanisms, help guide therapeutic choices, and assess the effectiveness of treatment response. [5][6][7] Two of the most important typological models of alcoholism are the classifications established by Cloninger et al 8 and Babor et al 9 Based on the genetic and environmental features of alcoholism vulnerability, Cloninger et al 8 discriminate two subtypes of alcoholism: type I and type II. In clinical terms, type I is defined by a later onset of problem drinking and fewer alcohol-related problems.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we could formulate the following research questions: Do alcoholism classification constructs remain valid in populations that present a lifetime diagnosis of alcohol dependence and a ''primary'' diagnosis of opiate or cocaine dependence? Additionally, how can we generalize the clinical findings achieved in alcoholism typologies studies 6 to these polydrug subtypes? For instance, results from psychosocial and pharmacological trials demonstrate that alcoholism subtype influences the benefit derived from specific alcoholism treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation